High genetic diversity among diarrheagenic Escherichia coli isolates from patients with acute diarrhea in Khuzestan province, Southwestern Iran. Issue 2 (April 2021) - Owlia, Parviz; Bouzari, Saeid; Saderi, Horieh; Ghanavati, Roya; Darbandi, Atieh
Abstract : Background: Diarrheagenic Escherichia coli (DEC) is an enteric pathogen that causes a wide variety of gastrointestinal diseases in developing countries. In our previous study, the prevalence of DEC pathotypes from acute diarrhea patients in Khuzestan province was determined. In this study, we investigated the antimicrobial resistance profile and molecular genetic characteristics of this isolate. Methods: Antibiotic susceptibility testing of bacterial isolates was determined by disc diffusion technique on Muller Hinton agar. The production of extended-spectrum beta-lactamases (ESBLs) was confirmed by the Double Disc Synergy Test (DDST). The genetic diversity of isolates was determinate by pulsed-field gel electrophoresis (PFGE). Results: Among all DEC strains, 100% were resistant to at least one commonly prescribed antibiotic. Strains were resistant to first-line antibiotics, such as tetracycline, ampicillin, and sulfamethoxazole-trimethoprim. Furthermore, 72% of DEC isolates were multidrug-resistant and aEPEC and STEC were the categories with a major proportion of this feature. ESBL-producing strains were observed in 38% of all DEC isolates. PFGE analysis showed 19 unique pulsotypes of 22 studied DEC pathotypes. However, a few isolates were found to be clonal (clusters A, B, and C). Conclusion: The current study provides novel information about the presence of DEC isolates particularly with the rate of high antibiotic resistance among acute diarrheal samples in Khuzestan, Iran. Our data revealed that there was almost high heterogeneity among isolated DEC pathotypes. Proper infection control policies are needed to be implemented in order for the infections to be effectively controlled.